Seismic velocity and Q anisotropy in fractured poroelastic media - Santos, Juan Enrique (2014)
A fluid-saturated poroelastic isotropic medium with aligned fractures behaves as a transversely isotropic and viscoelastic (TIV) medium when the predominant wavelength is much larger than the average distance between fractures. A planar fracture embedded in a fluid saturated poroelastic background medium can be modeled as a extremely thin and compliant porous layer. P-waves traveling in this type of medium induce fluid-pressure gradients at fractures and mesoscopic-scale heterogeneities, generating fluid flow and slow (diffusion) Biot waves, causing attenuation and dispersion of the fast modes (mesoscopic loss). A poroelastic medium with embedded aligned fractures exhibits significant attenuation and dispersion effects due to this mechanism, which can properly be represented at the macroscale with an equivalent TIV medium. In this work, we apply a set of compressibility and shear harmonic finite-element (FE) experiments on fractured highly heterogeneous poroelastic samples to determine the five complex and frequency dependent stiffnesses characterizing the equivalent medium. The experiments consider brine or patchy brine-CO2 saturated samples and a brine saturated sample with a heterogeneous (fractal) skeleton with fractures. We show that fractures induce strong seismic velocity and Q anisotropy, both for qP and qSV waves, enhanced either by patchy saturation or frame heterogeneity.